Selective harmonic elimination pulse width modulation for three-phase nine-level inverter using improved whale optimization algorithm - Bimazlim, Muhammad Aniq Shahmi; Ismail, Baharuddin; Aihsan, Muhammad Zaid; Ali, Rosnazri; Talib, Md Hairul Nizam; Muhammad Azhar Walter, Muhammad Sirajuddin; Mazalan, Siti Khodijah; Hafizi Rohani, Mohamad Nur Khairul (2023)
For many years, multilevel inverter (MLI) is a system well-known for converting DC voltage to AC voltage which is suitable for energy resources conversion for industrial power sources. With the help of Selective Harmonic Elimination Pulse Width Modulation (SHEPWM) switching technique, the output power from the MLI system is better efficiency with low Total Harmonics Distortion (THD). The SHEPWM switching technique is used to eliminate the lower order of the harmonics and reduces the Total Harmonics Distortion (THD) of the MLI system. Along with the optimization algorithms to solve difficult non-linear equations involving with SHEPWM, applying SHEPWM into MLI system helps to further improve the output power efficiency. Whale Optimization Algorithm (WOA) is one of the algorithms developed which capable of solving the non-linear equation and obtained suitable results for MLI. Additionally, many types of improvement done on WOA, called as Improved Whale Optimization Algorithms (IWOA) also developed to obtain better results compared with WOA. Developed in a MATLAB environment, a proposed IWOA is applied to solve the equation and compared with WOA. The results show that the proposed IWOA capable of achieving higher probability with fast convergence speed reaching global optimal compared to WOA. With the proposed approach, the IWOA efficiently computed required switching angles, to eliminate the selective lower-order harmonics for different modulation indices (Ma). In this paper, the proposed IWOA is performed on a three-phase nine-level cascaded H-bridge multilevel inverter (CHBMLI) for a wide range of modulation indexes between 0.1 until 1. The results show the eliminations of 5 th, 7th, and 11th harmonics from the output of the three-phase nine-level MLI system thus reducing THD from the system up to 5.82%.